Preparation method of electrode with phosphorus-doped induced Ti4O7 lattice strain and application of electrode in deep purification of electro-catalytic enhanced pharmaceutical wastewater
By in-situ phosphorus doping in the Ti4O7 electrode to regulate the lattice structure, construct a Ti-OP structure, adsorb CO32- and promote the generation of ·OH, the problems of low efficiency and high energy consumption of the Ti4O7 electrode in the electrocatalytic degradation of pharmaceutical wastewater were solved, and a high-efficiency and low-energy consumption antibiotic degradation effect was achieved.
Patent Information
- Application Number
- CN202510805315.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-17
- Publication Date
- 2025-09-12
- Estimated Expiration
- 2045-06-17
AI Technical Summary
Existing Ti4O7 electrode materials have low efficiency in the electrocatalytic degradation of pharmaceutical wastewater, and traditional modification methods increase energy consumption or cause secondary pollution, making it difficult to effectively inhibit the quenching effect of CO32- on ·OH.
By in-situ phosphorus doping to regulate the Ti4O7 lattice structure, a Ti-OP structure was constructed to adsorb CO32- and promote the generation of ·OH, inhibit the quenching of CO32-, form a directional electron migration channel, and achieve the stable generation of ·OH.
It achieves efficient and low-consumption degradation of antibiotics in pharmaceutical wastewater, simplifies the preparation process, reduces costs, and improves electrocatalytic performance.
Smart Images

Figure CN120622622A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of environmental engineering technology, relates to research on the preparation technology of phosphorus-doped Ti4O7 electrode materials, and relates to the preparation of a phosphorus-doped Ti4O7 electrode that induces lattice strain and its application in electrocatalytically enhanced deep purification of medical wastewater. Background Art
[0002] Two major challenges of this century are energy shortages and increasingly severe environmental pollution. As the world's population continues to grow at an unprecedented rate, the demand for clean and accessible water is also increasing. In addition, due to changes in human living standards and the development of industrialization, new pollutants or organic contaminants are released into water bodies, adding further pressure to the aquatic environment. As the world's largest producer and exporter of antibiotics, China inevitably produces a large amount of pharmaceutical wastewater containing high concentrations of antibiotic pollutants during the pharmaceutical production process. With the rapid development of the domestic pharmaceutical industry, the content of highly toxic and difficult-to-treat antibiotics remaining in water bodies continues to increase, posing a potential threat to ecosystems and human safety. However, traditional wastewater biological treatment technologies have low treatment efficiency and are insufficient to completely remove or degrade antibiotics in wastewater. In addition, they consume high energy and emit high carbon emissions, increasing the cost of pollutant treatment.
[0003] Electrocatalysis has the advantages of high treatment efficiency, no secondary pollution, and simple operation, and is widely used in the treatment of pharmaceutical wastewater. · OH) is one of the most important active species in the electrocatalytic system and has a strong oxidizing property (redox potential 2.8V). 2- Often considered to be · An effective quencher of OH, thereby inhibiting · OH plays a role. But there is currently no method to inhibit CO3 2- right · OH quenches the material. The carbonate radical (CO3 ·- ) is more selective, and CO3 in natural water ·- The steady-state concentration is higher than · OH, and therefore CO3 ·- It has potential application value in limiting the persistence of various organic pollutants. Ti4O7 has a high oxygen evolution potential (>2.5 V vs SHE), excellent electrical conductivity (1500 S cm −1 ) and corrosion resistance, and is one of the common electrocatalytic materials. The interface charge transfer rate of pure Ti4O7 material is relatively low, which leads to low mass transfer efficiency in the reaction system and the electrocatalytic process cannot produce sufficient ·OH is used for pollutant degradation. Therefore, it is necessary to adopt a modification strategy to improve the performance of Ti4O7 electrocatalytic degradation of pollutants. Based on the above problems, the articles "Photochemical degradation of oxytetracycline: Influence of pH and role ofcarbonate radical", "Defect Engineering on a Ti4O7 Electrode by Ce 3+ Doping for the Efficient Electrooxidation of Perfluorooctanesulfonate" by photoactivating CO3 in UV / H2O2 system 2- 、Ce 3+ The doped Ti4O7 electrode enhances the degradation of organic pollutants. Although the above research can inhibit CO3 2- right · The quenching effect of OH and the promotion of electron transfer on the surface of Ti4O7 electrode require the use of ultraviolet light sources, which increases energy consumption. At the same time, ultraviolet light has a high demand for device materials, which also increases the cost of device construction. 3+ The doping of metal ions such as ions on the surface of Ti4O7 electrode will cause irreversible dissolution, which will cause secondary pollution to the water body. In addition, the above-mentioned modified materials increase the surface active sites and promote the production of active species ( · There is still much room for improvement in terms of OH) production.
[0004] Therefore, this application selects Ti4O7 material as the anode substrate material, and constructs Ti-OP Ti and P dual reaction active sites by regulating the system lattice structure through in-situ P doping, wherein Ti 3+ As · The generation site of OH, Ti after P doping 3+ The ratio of oxygen vacancies and the increase in · Compared with metal doping, the non-metallic doping of P is that the P atoms form a stable coordination structure with the Ti ions in Ti4O7 through coordination bonds, which effectively inhibits the dissolution of non-metallic ions. As the reaction proceeds, Ti 3+ Will gradually decrease, Ti 4+ Gradually increasing, · The OH production rate is limited. The P site can adsorb CO3 2- , thereby inhibiting the · Quenching of OH. CO3 adsorbed on P site 2- After being activated, it is easy to lose electrons and turn into CO3 ·-, P doping and more oxygen vacancies construct a directional electron migration channel in the system (P→Ti 3+ ), inhibiting Ti 3+ The trend of transformation to high valence state, thus · OH can be produced continuously and stably, achieving the goal of electrocatalytically degrading antibiotics in pharmaceutical wastewater with high efficiency and low consumption. Summary of the Invention
[0005] The present invention provides a method for preparing a P-doped titanium dioxide electrode (Ti4O7-P) material, and applies it to the electrocatalytic activation of CO3 2- Degradation of antibiotics in pharmaceutical wastewater. By constructing a Ti-OP structure, the PO bond can adsorb CO3 2- , thereby inhibiting the · Quenching of OH. 3+ As · The generation site of OH, Ti after P doping 3+ The ratio of oxygen vacancies increases and promotes · The generation of OH. As the reaction proceeds, Ti 3+ Will gradually decrease, Ti 4+ Gradually increasing, · The rate of OH generation is limited. CO3 adsorbed on the PO bond 2- Easily loses electrons and turns into CO3 ·- , P doping and more oxygen vacancies promote electron transfer to Ti 4+ ,make · OH can be produced continuously and stably, achieving the goal of efficient electrocatalytic degradation of antibiotics in pharmaceutical wastewater.
[0006] The technical solution of the present invention:
[0007] A method for preparing an electrode by phosphorus doping to induce Ti4O7 lattice strain, comprising the following steps:
[0008] An electrode plate with a Ti4O7 film sprayed on its surface and sodium hypophosphite monohydrate are placed in two porcelain boats respectively, and then the two porcelain boats are placed in the middle of a tube furnace, and the sodium hypophosphite monohydrate is placed upwind of the tube furnace, with a distance of 4-6 cm between the electrode plate and the sodium hypophosphite monohydrate; under a nitrogen atmosphere, the heating rate is 0.5-5°C / min, the reaction temperature is 250-400°C, the reaction time is 1-4 h, and the calcination is completed and the plate is naturally cooled to room temperature; after removing the electrode plate, it is placed in an electrochemical reduction reaction device as a cathode, a lead oxide electrode as an anode, and an ammonium fluoride solution as the electrolyte at 5 mA / cm 2 The Ti4O7 lattice strain electrode was obtained by operating in constant current mode for 2 minutes.
[0009] The thickness of the Ti4O7 film layer is 50-100 μm.
[0010] The ratio of the area of the electrode plate to the amount of sodium hypophosphite monohydrate added is 0.1-1.0 g of sodium hypophosphite monohydrate added per square centimeter of electrode.
[0011] The ammonium fluoride solution is a mixture of ethylene glycol, ammonium fluoride and water in a mass ratio of 90:2:8.
[0012] An application of a Ti4O7 lattice strain electrode in electrocatalytically enhanced deep purification of pharmaceutical wastewater comprises the following steps:
[0013] An electrochemical degradation system was constructed with Ti4O7 lattice strain electrode as anode and Ti plate as cathode; at 1-20 mA / cm 2 Under constant current conditions, the reaction temperature is 24℃-26℃, and the target is SMX wastewater with a concentration of 5-40 mg / L. CO3 2- When the content is 1-10mM and the reaction time is 30 min, the SMX degradation rate can reach more than 99%.
[0014] Beneficial effects of the present invention: In the method of the present invention, the lattice structure of the system is regulated by in-situ P doping Ti4O7, thereby improving the system's CO3 2- Activate and strengthen · The OH generation rate is increased to achieve efficient and low-cost degradation of antibiotics in pharmaceutical wastewater. The PH3 generated by the in-situ P doping process in step 1 undergoes a redox reaction on the Ti4O7 surface, forming a large number of new O vacancies. At the same time, P is doped into the Ti-OP structure in the Ti4O7 lattice structure. O vacancies can induce the formation of localized Mixed valence network, through the small polaron hopping mechanism to achieve rapid electron migration in the system. Each time an O vacancy is formed, two Ti³ sites, directly increasing the density of surface active sites. The active site weakens the OH bond by coordination, promoting H O dissociation generates · OH. Reasonable construction of P sites and the use of adjustable local electronic microenvironment can achieve its effect on CO3 2- Adsorption and activation, thereby reducing its conversion into CO3 ·- Reaction energy barrier, inhibiting CO3 2- right · If the P doping amount is insufficient, the P atoms cannot be fully embedded in the Ti-O lattice and cannot form sufficient lattice strain, resulting in a limited concentration of oxygen vacancies and the number of exposed active sites, which affects the activity of the redox reaction on the electrode surface. At the same time, low-concentration P doping is difficult to effectively control The conduction band and valence band positions of the material lead to an unsatisfactory distribution of the electronic state density on the surface of the material, an insignificant improvement in conductivity, and a reduction in the adsorption and activation capacity of the reaction intermediates. The imbalance of the ratio causes the center of the catalyst d band to move upward excessively, and the adsorption of the intermediate product is too strong (such as · OH), hindering subsequent reaction steps. High concentrations of P doping cause lattice distortion accumulation, resulting in distortion or even partial collapse of the Ti-O octahedral structure, reducing the mechanical stability and cycle life of the material. Excessive heating rates can lead to insufficient diffusion of P atoms, resulting in the formation of P-rich in local areas and inactive phosphorus oxide layers (such as PO ), causing lattice stress concentration, resulting in microcracks and grain boundary embrittlement. Slow heating will prolong the high temperature residence time, causing P elements to segregate to the grain boundaries (the P concentration at the grain boundaries is 3-5 times that of the bulk phase), forming an inactive TiPO4 interface layer, which hinders electron transmission. At the same time, CO3 ·- During the process, CO3 2- The electrons are transferred to the electrode surface, and the electrons can effectively migrate to the Ti 3+ sites, inhibiting its tendency to transform to a high valence state during catalysis, thereby achieving · OH is generated stably and efficiently. Therefore, this material can achieve CO3 2- Existence · The stable generation of OH allows for efficient electrocatalytic degradation of antibiotics. Furthermore, the preparation method is simple and low-cost, suggesting potential for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 This is a sample picture of Ti4O7-P electrode material.
[0016] Figure 2 TEM elemental surface scan of Ti4O7-P electrode material, where (a) is the P element surface scan and (b) is the Ti, O, and P element surface scan.
[0017] Figure 3 This is the XRD pattern of Ti4O7-P electrode material.
[0018] In the figure: 1 DC power supply; 2 Ti4O7-P electrode; 3 titanium plate. DETAILED DESCRIPTION
[0019] The specific implementation of the present invention is described in detail below in conjunction with the technical solutions and drawings.
[0020] Example 1
[0021] Preparation method of Ti4O7-P electrocatalytic material:
[0022] 3 g of sodium hypophosphite monohydrate was placed in a porcelain boat, placed upstream of a tube furnace, and a Ti4O7 electrode was placed downstream. The boat was calcined in a tube furnace with N2 protection, a heating rate of 3°C / min, a reaction temperature of 350°C, and a reaction time of 2 h. After the reaction was completed and cooled to room temperature, the electrode was removed and washed alternately with deionized water and ethanol twice, and reduced with 1 M (NH4)2SO4 solution for 5 min. The reduction reaction apparatus was as follows: Figure 1 As shown, a P-modified Ti4O7 electrode Ti4O7-P3-3 was obtained.
[0023] TEM elemental surface scan ( Figure 2 ) shows that P, Ti and O elements are evenly distributed in the material, indicating that P has been successfully doped into the Ti4O7 lattice. XRD spectrum ( Figure 3 ) showed that all Ti4O7-P samples retained diffraction peaks consistent with Ti4O7 (20.76°, 29.57°, and 31.74°), matching those of a standard card (PDF#50-0787). All Ti4O7-P samples exhibited a new characteristic peak at 2θ=22.84°, and the intensity of the diffraction peak at 29.57° increased significantly, indicating that the PH3 etching process removed the original Ti4O7 surface layer and formed a new Ti4O7 crystalline phase. Furthermore, the diffraction peak at 53.31° shifted slightly to higher angles after P doping, indicating that the introduction of P caused local distortion of the Ti4O7 crystal structure.
[0024] The above method was used to select different heating rates of 1, 2, 5, and 10°C / min to prepare a series of Ti4O7-P materials (named Ti4O7-P3-1, Ti4O7-P3-2, Ti4O7-P3-5, and Ti4O7-P3-10) for subsequent performance comparison tests.
[0025] In addition, the above method was used to select different dosages of sodium hypophosphite monohydrate of 1, 2, 5, and 7 g to prepare a series of Ti4O7-P materials (named Ti4O7-P1-3, Ti4O7-P2-3, Ti4O7-P5-3, and Ti4O7-P7-3) for subsequent performance comparison tests.
[0026] Example 2
[0027] Electrocatalytic activation of CO3 2- Degradation of sulfamethoxazole: 3mM Na2CO3 was weighed and dispersed into an electrocatalytic reactor containing 50mL sulfamethoxazole (20mg / L SMX). A series of Ti4O7-P material electrodes were used as anodes, a Ti plate was used as cathodes, and the current density was 5mA / cm 2The electrolyte was 30 mM Na₂SO₄, and the reaction time was 30 minutes. The reaction solution was sampled every 10 minutes, filtered through a 0.22 μm filter, and 1 mL was sampled for instrumental analysis to determine the degradation rate. After the 30-minute reaction, another 15 mL of the reaction solution was sampled and filtered through a 0.22 μm filter to measure the TOC removal rate during the degradation process.
[0028] The SMX concentration was determined by ultra-high performance liquid chromatography. The test results showed that after 30 min of reaction, CO3 2- A series of Ti4O7-P materials demonstrated SMX degradation rates exceeding 99%, compared to a pure Ti4O7 electrode, which only achieved a 15% SMX degradation rate. A comparison of SMX mineralization performance revealed that Ti4O7-P3-3 achieved a 65% mineralization rate after 30 minutes of reaction, outperforming other materials in the series (mineralization rates ranged from 30% to 47%). Ti4O7-P3-3 completely degraded SMX in solution (99.9% removal rate) within 20 minutes of reaction, surpassing other materials in the series, and was therefore selected for subsequent performance comparison testing.
[0029] Example 3
[0030] Electrocatalytic activation of CO3 2- Degradation test of different pollutants: Same as Example 2, except that SMX was replaced with the same concentrations of electron-rich pollutants: ciprofloxacin (CIP), diclofenac (DCF), minocycline (MINO) and electron-deficient pollutants: carbamazepine (CBZ), amoxicillin (IBF). Ultra-high performance liquid chromatography (UPLC) showed that the degradation rates of electron-rich pollutants CIP, DCF, and MINO were all above 99%, while the degradation rates of electron-deficient pollutants CBZ and IBF were 89.1% and 95.1%, respectively, indicating that P-doped Ti4O7 electrocatalyzed the activation of CO3 2- The system has high applicability to electron-rich pollutants.
[0031] Example 4
[0032] Effect of ions and natural organic matter on electrocatalytic degradation performance: cations: potassium ion (KNO3), calcium ion (Ca(NO3)2), magnesium ion (Mg(NO3)2); anions: nitrate ion (KNO3), chloride ion (NaCl); natural organic matter (humic acid) and 3mM CO3 2- 50 mL of SMX solution (20 mg / L) was added to the electrocatalytic reactor. Ti4O7-P electrode was used as anode and Ti plate was used as cathode. The current density was 5 mA / cm 2The electrolyte was 30 mM Na₂SO₄, and the reaction time was 30 minutes. The reaction solution was sampled every 10 minutes, filtered through a 0.22 μm filter, and 1 mL was sampled for instrumental analysis to determine the degradation rate. This degradation efficiency was compared with that of SMX without the addition of anions or cations, demonstrating the influence of anions and cations, as well as natural organic matter, on the degradation efficiency.
[0033] The test results show that after adding potassium ions and nitrate ions, the degradation efficiency of SMX has not changed significantly. High content of calcium ions, magnesium ions and chloride ions will inhibit the degradation of SMX, and Cl ions will react with CO3 2- Competitive effects occur, calcium and magnesium ions will react with CO3 2- The formation of precipitation inhibits its participation in the degradation reaction. The addition of natural organic matter will also affect the degradation of SMX, which may be caused by the competitive reaction between natural organic matter and SMX during the degradation process.
[0034] Example 5
[0035] Application test of Ti4O7-P electrode in actual wastewater: SMX solution (20 mg / L) was prepared with seawater, tap water, and domestic sewage treatment plant water. 3 mM CO3 was added to the electrocatalytic reactor containing 50 mL of SMX solution (20 mg / L). 2- The Ti4O7-P3-3 electrode was used as the anode and the Ti plate was used as the cathode. The current density was 5 mA / cm 2 The electrolyte was 30 mM Na₂SO₄, and the reaction time was 30 minutes. The reaction solution was sampled every 10 minutes, filtered through a 0.22 μm filter membrane, and 1 mL was sampled for instrumental testing to determine the degradation rate. The degradation efficiency was compared with that of SMX prepared with pure water, demonstrating the impact of actual wastewater on the degradation efficiency.
[0036] In addition, 3 mM CO3 was added to the electrocatalytic reactor filled with 50 mL of actual pharmaceutical wastewater (initial COD of 1500 mg / L). 2- , with P-doped Ti4O7 electrode as anode and Ti plate as cathode, the current density is 10mA / cm 2 The electrolyte was 30 mM Na₂SO₄, and the reaction time was 30 min. After the 30 min reaction, 15 mL of the reaction solution was filtered through a 0.22 μm filter membrane, and the COD and BOD changes during the degradation process were measured.
[0037] The test results show that the degradation rate of SMX in seawater and tap water matrices has increased. In the influent matrix of domestic sewage treatment plants, the degradation efficiency of SMX has dropped significantly. It is possible that there is a competitive relationship between COD and SMX in the influent, which limits the interaction between active oxidative species and SMX. Although the degradation efficiency has decreased, Ti4O7-P3-3 has a significant effect on CO3 2- The activation process continued to work in the treatment station's influent matrix. The COD content of the pharmaceutical wastewater decreased by 63.6%, and the BOD / COD ratio increased by 40.3%, demonstrating that the system can improve the biodegradability of wastewater in a short period of time.
Claims
1. A method for preparing a Ti4O7 electrode by phosphorus doping and inducing lattice strain, characterized in that: Here are the steps: An electrode plate with a Ti4O7 film sprayed on its surface and sodium hypophosphite monohydrate are placed in two porcelain boats respectively, and then the two porcelain boats are placed in the middle of a tube furnace, and the sodium hypophosphite monohydrate is placed upwind of the tube furnace, with a distance of 4-6 cm between the electrode plate and the sodium hypophosphite monohydrate; under a nitrogen atmosphere, the heating rate is 0.5-5°C / min, the reaction temperature is 250-400°C, the reaction time is 1-4 h, and the calcination is completed and the plate is naturally cooled to room temperature; after removing the electrode plate, it is placed in an electrochemical reduction reaction device as a cathode, a lead oxide electrode as an anode, and an ammonium fluoride solution as the electrolyte at 5 mA / cm 2 The Ti4O7 lattice strain electrode was obtained by running the device in constant current mode for 2 min.
2. The electrode preparation method according to claim 1, characterized in that: The thickness of the Ti4O7 film layer is 50-100 μm.
3. The electrode preparation method according to claim 1, characterized in that: The ratio of the area of the electrode plate to the amount of sodium hypophosphite monohydrate added is 0.1-1.0 g of sodium hypophosphite monohydrate added per square centimeter of electrode.
4. The electrode preparation method according to claim 1, characterized in that: The ammonium fluoride solution is a mixture of ethylene glycol, ammonium fluoride and water in a mass ratio of 90:2:
8.
5. An application of a Ti4O7 lattice strain electrode obtained by the electrode preparation method according to any one of claims 1 to 4 in electrocatalytic enhanced deep purification of pharmaceutical wastewater, characterized in that: Here are the steps: An electrochemical degradation system was constructed with Ti4O7 lattice strain electrode as anode and Ti plate as cathode; at 1-20 mA / cm 2 Under constant current conditions, the reaction temperature is 24℃-26℃, and the target is SMX wastewater with a concentration of 5-40 mg / L. CO3 2- When the content is 1-10mM and the reaction time is 30 min, the SMX degradation rate can reach more than 99%.
Citation Information
Patent Citations
Self-supporting electro-catalytic hydrogen evolution catalyst electrode with strain lattice and preparation method and application of self-supporting electro-catalytic hydrogen evolution catalyst electrode
CN115323395A
Preparation method and application of co-doped modified Ti4O7 electrode and electrode
CN119456046A
Water treatment system for removing PFOA (perfluorooctanoic acid) in soil washing wastewater through electrooxidation coupled hydrogen peroxide reduction and application of water treatment system
CN119750723A
Fuel cell anode structure for voltage reversal tolerance
US20080187813A1
